Time and Its Measurement - Arthur, James, 1842-1930 (Salt Lake City, UT : Project Gutenberg, 2014)
"Time and Its Measurement" by James Arthur is a scientific publication written in the early 20th century. The work explores various aspects of time and its historical measurement, including ancient methods and modern advancements in timekeeping devices. The text covers a range of topics from early sundials and water clocks to the intricacies of astronomical foundations that govern our understanding of time. At the start of the book, the author presents an abstract overview of time, discussing how humanity has grappled with defining it. The opening chapter outlines the evolution of time measurement from ancient civilizations, referencing biblical accounts of time divisions, and touches upon early devices like sundials and water clocks. Arthur's insights bridge historical context with scientific principles, demonstrating how human perceptions and methodologies in measuring time have developed over millennia. The text not only delves into practical applications but also contemplates philosophical questions surrounding the nature of time itself. (This is an automatically generated summary.)
Release date is 2014-02-07
E-text prepared by Chris Curnow, RichardW, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Clocks and watches; Time